Interconexões na integração lusófona: expressões idiomáticas e interculturalidade - Valadares, Flavio Biasutti (2019)
The research addresses the possibilities ofinterconnectedness in the Lusophone space based on theidea of identity construction through the use of idiomaticexpressions, highlighting the integration in the world ofLusophony. It aims to discuss the interconnection in aninterface of integration related to the Constitution of alusophone identity whose space is organized with the use ofcommon idiomatisms in various production environments,highlighting such space as conducive to the discussion ofInterculturality. It is based on lusophone and the concept ofidiomatic expressions, in addition to the perspective ofinterculturality. As methodological procedures, it collectsjournalistic texts for analysis in sites of countries with officialPortuguese language. It concludes that the notion that theeffects of meaning are produced in a substantiated wayfrom what idiomatic expressions can assume as to thesignification that the metaphors inscribe themselvespromote for the construction of an interculturality.